Mycorrhizal fungi inoculation and phosphorus fertilizer on growth, essential oil production and nutrient uptake in peppermint (Mentha piperita L.) - Arango,M.C. (2012)
This study evaluated the effects of inoculation with the arbuscular mycorrhizal fungi Glomus mosseae, Glomus intraradices A4 and Glomus intraradices B1 and two phosphorus levels (10 and 40 mg kg-1) on root colonization, plant growth, nutrient uptake and essential oil content in Mentha piperita L. The experiment was carried out in a greenhouse, in 4x2 factorial arrangement, in completely randomized design. At sixty days after transplanting, the mycorrhizal plants had significantly higher fresh matter, dry matter and leaf area compared to non-mycorrhizal plants. The inoculation increased P, K and Ca levels in the shoot which were higher under 40 mg P kg-1 of soil. Plants grown with 40 mg P kg-1 soil increased the essential oil yield per plant by about 40-50% compared to those cultivated with 10 mg P kg-1, regardless of the mycorrhizal treatment. Among the studied fungal species, inoculation with G. intraradices A4 and a high level of P significantly increased plant growth and essential oil yield, compared to the other studied mycorrhizal fungal species. In conclusion, inoculation of arbuscular mycorrhizal fungi into peppermint plants is a feasible alternative to increase the essential oil production and reduce the use of fertilizers required to obtain economic production of peppermint under phosphorus-deficient soil condition.